2000
DOI: 10.1097/00008571-200011000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of a new variant of the CYP2A6 gene (CYP2A6*1B) apparently diagnosed as heterozygotes of CYP2A6*1A and CYP2A6*4 C

Abstract: During the course of investigating the frequency of a CYP2A6 whole deletion-type polymorphism (CYP2A6*4C) in Japanese, an unexpectedly large population of heterozygotes for CYP2A6*4C and the wild-type (CYP2A6*1A) was found. Cloning of a cDNA encoding CYP2A6 from the liver of individuals judged as heterozygotes for CYP2A6*4C and the CYP2A6*1A was carried out to identify the causal allele(s) responsible for a possible overestimation. A clone isolated from the liver cDNA library possessed 58 bp sequences in the 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 18 publications
3
64
3
Order By: Relevance
“…4,5 11 observed that subjects with the same reduced-activity alleles were not less likely to smoke. Loriot et al, 12 observed no difference in the smoking status according to the CYP2A6 genotype.…”
Section: Allele Frequencymentioning
confidence: 99%
See 2 more Smart Citations
“…4,5 11 observed that subjects with the same reduced-activity alleles were not less likely to smoke. Loriot et al, 12 observed no difference in the smoking status according to the CYP2A6 genotype.…”
Section: Allele Frequencymentioning
confidence: 99%
“…32 CYP2A6 gene was analysed for the gene conversion in the 3 0 -flanking region adjacent to exon 9 (CYP2A6*1B) and the deletion type (CYP2A6*4A) according to a method reported by Ariyoshi et al 4 In brief, a region ranging from exon 8 of the CYP2A7 gene or CYP2A6 gene to a 3 0 -untranslated region in exon 9 of the CYP2A6 gene was amplified, and then digested by the restriction enzymes, AccII and Eco81I. The CYP2A6*1A genotype was defined according to Ariyoshi et al 4 as 'wild type' but may carry undetected mutations in other regions than the one explored.…”
Section: Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the genotyping method by Ariyoshi et al, 15 the primer set of 2A6-B4 and 2A6UTR-AS1 was used (Figure 6a). The 2A6-B4 primer can anneal to exon 8 of both the CYP2A6 and CYP2A7 genes.…”
Section: T Fukami Et Almentioning
confidence: 99%
“…Restriction enzymes were 15 and Nakajima et al 14 The primers of 2A6-B4 15 and 2Aint7F 14 anneal to both the CYP2A6 and CYP2A7 genes. The primers of 2A6UTR-AS1 15 and 2A6R2 14 anneal to the CYP2A7 polymorphic alleles (CYP2A7*1B, CYP2A7*1C and CYP2A7*1D) as well as the CYP2A6 gene, resulting in the misgenotyping of CYP2A6*4. (b) Method by Oscarson et al 8 The primer of 2Aex7F anneals to both the CYP2A6 and CYP2A7 genes.…”
Section: Chemicals and Reagentsmentioning
confidence: 99%